2011 IEEE International Ultrasonics Symposium 2011
DOI: 10.1109/ultsym.2011.0459
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear elastic model for predicting triple beat in SAW duplexers

Abstract: This paper proposes simple and precise nonlinear simulation techniques for surface acoustic wave (SAW) duplexers, especially for the in-band 3rd order nonlinear distortion, the socalled 'triple beat'. The simulation model is based on the nonlinearity of SAW stress vs. strain (nonlinear elasticity of SAW), and needs just one nonlinear parameter, which represents the 3rd order nonlinear coefficient for the elastic constant. The simulation results of the triple beat for 1.9 GHz Personal Communications Service (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…The source of the nonlinearity may refer to the mechanisms from the piezoelectric constitutive equations [6]. As they satisfy the piezoelectric constitutive equations:…”
Section: Generation Mechanism Of Nonlinearitymentioning
confidence: 99%
See 1 more Smart Citation
“…The source of the nonlinearity may refer to the mechanisms from the piezoelectric constitutive equations [6]. As they satisfy the piezoelectric constitutive equations:…”
Section: Generation Mechanism Of Nonlinearitymentioning
confidence: 99%
“…Even so, research teams including Qorvo, Murata, and Chiba University [3,6,[8][9][10][11][12][13]22,31] have built and implemented the measurement systems on harmonics and intermodulation of nonlinearity for SAW devices. Moreover, our team also developed a harmonics and intermodulation measurement platform for SAW resonators, filters, and duplexers both on-chip and on PCB board.…”
Section: Experimental Measurement For Nonlinear Signalsmentioning
confidence: 99%
“…A simulation model of nonlinear effects in SAW components is required in order to better characterize, model, and minimize the nonlinearities. The generation of IMD3 caused by the nonlinearity of SAW devices has been studied by several authors based on simplified models such as P-matrix [3], [4], coupling of modes [5], [6], or the Mason model [7], and more recently a model based on the finite element method (FEM) [1], [2], [8]. Fig.…”
Section: Investigation On Third-order Intermodulationmentioning
confidence: 99%
“…Using the electroelasticity theory, it was shown that a nonlinear P-matrix simulation model using a single frequencyindependent effective nonlinearity constantĈ(η), which may depend on the metallization ratio (η), can predict the IMD3 of a layered system very well [3], [5], [8]. In [2] and [8], this very same effective nonlinear constant was theoretically evaluated using a FEM approach, where linear fields, associated with input tones, are combined with the nonlinear material tensor data to obtain the sources of nonlinear fields.…”
Section: Investigation On Third-order Intermodulationmentioning
confidence: 99%
“…This concern led to extend the research on modeling and simulation of the nonlinearities of SAW devices during the last two decades [1]- [11]. These references used different approaches, for example, based on finite element model (FEM) [1], circuit-level design techniques [2], [3], Coupling of Modes (COM) theory [4]- [8] or P-Matrix [9]- [11]. Despite of the different published approaches, there is still a lack of generalized consensus about the origin of the nonlinear behaviour.…”
Section: Introductionmentioning
confidence: 99%